Comparison of double-layer large-diameter and conventional small-diameter plastic stents for preoperative biliary drainage in resectable distal malignant biliary obstruction - Matsubara, Tokuhiro (Sci Rep, 2020)
The use of a plastic stent (PS) in resectable patients with distal malignant biliary obstruction (DMBO) is uncommon due to the high failure rate of this method. This study evaluated the efficacy and safety of a double-layer, large-diameter PS as a bridge to surgery compared with a conventional PS. This was a single-center retrospective cohort study. In total, 129 consecutive patients with DMBO underwent pancreaticoduodenectomy between January 2011 and March 2018. Fifty-five patients who preoperatively underwent plastic biliary drainage were enrolled. The patients were divided into two groups based on stent diameter: a large-diameter plastic stent (LPS) group and a small-diameter plastic stent (SPS) group. The primary endpoint was the stent patency period, and the secondary endpoint was the medical cost. Thirty-six patients received SPSs; 19 patients received LPSs. The patency rate until surgery was significantly higher in the LPS group than in the SPS group (89.5% vs. 41.7%, P = 0.0006). Multivariate analysis revealed that LPS use was significantly associated with sufficient stent patency. The total cost of LPS use was significantly lower than that of SPS use. LPSs had longer patency and reduced medical costs than SPSs. LPSs may be suitable for patients with DMBO who are scheduled to undergo surgery.